Cottonseed protein concentrate (CPC) suppresses immune function in different intestinal segments of hybrid grouper ♀Epinephelus fuscoguttatus×♂Epinephelus lanceolatu via TLR-2/MyD88 signaling pathways. Issue 81 (October 2018) - Yin, Bin; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Chi, Shuyan; Yang, Qihui; Zhang, Shuang; Chen, Liqiao
Abstract: Cottonseed protein concentrate (CPC) has similar amino acid composition compared with fish meal, and has the characteristics of low gossypol and low toxicity. The present study was conducted to investigate the growth performance, antioxidant capacity and different intestinal segments immune responses of hybrid grouper to replacement dietary fish meal ofCPC. Six iso-nitrogenous (50% crude protein) and iso-lipidic (10% crude lipid) diets were formulated: a reference diet (FM) containing 60% fishmeal and five experimental diets (12%, 24%, 36%, 48 and 60%) in which fishmeal protein was substituted at different levels by CPC to feed fish (initial body weight: 11 ± 0.23 g) for 8 weeks. Thena challenge test with injection of Vibrio parahaemolyticus was conducted for 7 days until the fish stabilized. The results showed that specific growth rate (SGR) was the highest with 24% replacement level and feed conversion ratio (FCR)was significantly increased when the replacement level reached 48% ( P  < 0.05). The content of malonaldehyde (MDA) in the serum was significantly increased when the replacement level reached 36% ( P  < 0.05). The plica height in the proximal, mid and distal intestine were significantly decreased with the replacement level up to 48% ( P  < 0.05). Hepatic fat deposition wasaggravatedwhen the replacement level reached 36% ( P  < 0.05). The expression of IL-6, TNF-α, and IL-1β mRNAs were significantly up-regulated ( P  < 0.05). The hepcidin mRNA expression was significantly down-regulated ( P  < 0.05). In proximal intestine (PI) and mid intestine (MI), IFN-γ mRNA expression was significantly up-regulated ( P  < 0.05). These results suggested that the CPC decreased hybrid grouper growth performance and inflammation function, and different inflammation function responses in PI, MI, and distal intestine (DI) were mediated partly by the TLR-2/MyD88 signaling pathway. According to the analysis of specific growth rate, the dietary optimum replacement level and maximum replacement level were estimated to be 17% and 34%, respectively. Highlights: Cottonseed protein concentrate (CPC) has the characteristics of low gossypol and low toxicity. The mechanism of immune response in different intestinal segments differs with the replacing fish meal by CPC. The TLR2/MyD88 signaling pathway plays a key role in intestinal inflammation induced by CPC in place of fish meal.